2018
DOI: 10.1039/c7cy02194a
|View full text |Cite
|
Sign up to set email alerts
|

Steel-based electrocatalysts for efficient and durable oxygen evolution in acidic media

Abstract: 2High overpotentials, particularly an issue of common anode materials, hamper the process of water electrolysis for clean energy generation. Thanks to immense research efforts up to date oxygen evolution electrocatalysts based on earth-abundant elements work efficiently and stably in neutral and alkaline regimes. However, non-noble metal-based anode materials that can withstand low pH regimes are considered to be an indispensable prerequisite for the water splitting to succeed in the future.All oxygen evolving… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 77 publications
3
32
0
Order By: Relevance
“…Recently Schäfer and Chatenet showed that surfacemodified (stainless) steel can be used as water splitting electrodes. [14] The approaches shown by Chatenet et al [15] and Schäfer et al [16][17][18][19] and by some of other groups are taking advantage of the elements contained in steel like Fe, Ni and Co, known for their sophisticated properties (at least) towards the electrocatalytically-initiated OER. However, scientists failed, likely owing to the absence of noble ingredients, in rendering steel at least as active towards the HER as Pt is.…”
Section: Silent Conditionsmentioning
confidence: 99%
“…Recently Schäfer and Chatenet showed that surfacemodified (stainless) steel can be used as water splitting electrodes. [14] The approaches shown by Chatenet et al [15] and Schäfer et al [16][17][18][19] and by some of other groups are taking advantage of the elements contained in steel like Fe, Ni and Co, known for their sophisticated properties (at least) towards the electrocatalytically-initiated OER. However, scientists failed, likely owing to the absence of noble ingredients, in rendering steel at least as active towards the HER as Pt is.…”
Section: Silent Conditionsmentioning
confidence: 99%
“…substantially.T ot he besto fo ur knowledge, some of our group were the first to tailor steel intentionally into outstanding,e fficient, and stable OER electrocatalysts [56][57][58] on the basis of, inter alia, thin Ni, Fe oxide layers firmly attachedt ot he iron-based matrix. Benchmark OER properties were showna tp H13a nd pH 14, as the overpotential (h)a mounted to 212 mV at 12 mA cm À2 in 1 m KOH and to 269.2 mV at 10 mA cm À2 in 0.1 m KOH, respectively.V ery recently,h ydrothermal/electrochemicalo xidation of CrNi-based steel [59] as well as the surface oxidation of Ni42 [60] and X20CoCrWMo10-9//Co 3 O 4 steel [57,61] also provedt ob es uitable for the efficient preparation of acceptable OER catalysts that weres table and workedo ver a wide pH range.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches shown by Chatenet et al . and Schäfer et al . and by some of other groups are taking advantage of the elements contained in steel like Fe, Ni and Co, known for their sophisticated properties (at least) towards the electrocatalytically‐initiated OER.…”
Section: Resultsmentioning
confidence: 99%